Policy making for emotional support: Tackling loneliness in migrant domestic workers - Lopez Fernandez, Rosalia (European Public & Social Innovation Review, 2025)
Introduction: The article delves into the experience of loneliness among migrant women employed as domestic workers in Spain, shedding light on the intersections of gender, race, and migrant status. Methodology: Employing a constructivist grounded theory approach, the study conducted 31 in-depth interviews with migrant women working as domestic workers. Results: The analysis first demonstrates that the feeling of loneliness is predominantly influenced by the characteristics of the migration process and their subsequent integration into domestic work. Factors exacerbating loneliness include separation from loved ones, the challenging working conditions that limit their leisure time and privacy, and the absence of emotional and social support. Secondly, the results highlight the psychological and physical consequences of loneliness. Discussion: The research underscores the importance of implementing social innovation policies to address and alleviate the effects of loneliness on this vulnerable group. It highlights that loneliness is not only an individual emotional experience but also a structural consequence of their living and working conditions. Conclusion: The study emphasizes the urgent need for proactive measures to mitigate the impact of loneliness on migrant women working as domestic workers in Spain. It acknowledges the intricate interplay of individual and structural factors that influence their overall well-being.